2015
DOI: 10.1007/s00198-015-3391-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of osteoporosis with genetic variants of circadian genes in Chinese geriatrics

Abstract: For the first time, we show that Cry 2 rs2292910 and MTNR1B rs3781638 are associated with osteoporosis in a Chinese geriatric cohort. Therefore, targeting the abnormalities of the CRY2 and MTNR1B genes may be a potential strategy to treat and/or to prevent osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…124 Curiously, lipocalin 2, a recently identified ligand of MC4R, is secreted by osteoblasts in mice and signals to suppress appetite by binding MC4R-expressing hypothalamic neurons 125 ; MC4R polymorphisms have also been associated with early-onset obesity. 126 Mutation of CNR2 21 and MTNR1B 127 had an additional association with human osteoporosis. Karsak et al found that two missense variants (the double single-nucleotide polymorphism (SNP) rs2502992–rs2501432 and Gln63Arg; rs2229579 and His316Tyr) are associated with osteoporosis in postmenopausal Caucasian women, 21 while Li et al found that MTNR1B rs3781638 is associated with osteoporosis in Chinese geriatrics.…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 99%
See 1 more Smart Citation
“…124 Curiously, lipocalin 2, a recently identified ligand of MC4R, is secreted by osteoblasts in mice and signals to suppress appetite by binding MC4R-expressing hypothalamic neurons 125 ; MC4R polymorphisms have also been associated with early-onset obesity. 126 Mutation of CNR2 21 and MTNR1B 127 had an additional association with human osteoporosis. Karsak et al found that two missense variants (the double single-nucleotide polymorphism (SNP) rs2502992–rs2501432 and Gln63Arg; rs2229579 and His316Tyr) are associated with osteoporosis in postmenopausal Caucasian women, 21 while Li et al found that MTNR1B rs3781638 is associated with osteoporosis in Chinese geriatrics.…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 99%
“…Karsak et al found that two missense variants (the double single-nucleotide polymorphism (SNP) rs2502992–rs2501432 and Gln63Arg; rs2229579 and His316Tyr) are associated with osteoporosis in postmenopausal Caucasian women, 21 while Li et al found that MTNR1B rs3781638 is associated with osteoporosis in Chinese geriatrics. 127 The ADRB2 polymorphism (rs1042714) was also associated with heterotopic ossification in adult trauma patients with fractures. 128 EDG2 26 and H4R 23 were associated with human osteoarthritis (OA) in Japanese people.…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 99%
“…Moreover, mice lacking CRY1 and CRY2 exhibit increased bone volume [ 91 ]. In a Chinese pediatric cohort, Cry2 rs2292910 was associated with osteoporosis (r = -0.082, p = 0.045) [ 96 ].…”
Section: Peripheral Oscillators In Bonementioning
confidence: 99%
“…To be able to understand the role of the circadian clock system thoroughly, not only presence and function have to be investigated, but also demonstrating consequences of dysregulation is of importance. Interruption of the circadian clock mechanisms gave hints to implications in various diseases as diabetes [12, 13], osteoporosis [14], cancer [15] and immune-allergic diseases [16]. Finding the links between the circadian clock and diseases is of particular importance these days, since modern living comes along with numerous factors, which disturb circadian rhythms: artificial light of different sources being available at all times, irregular food uptake, shift work and so on.
Fig.
…”
Section: Introductionmentioning
confidence: 99%